Factors affecting owners’ choice of nutritional supplements for use in dressage and eventing horses - Gemmill, R.; Agar, C.; Freeman, S.L.; Hollands, T. (BMJ Publishing Group, 2016)
The aim of this study was to investigate the factors affecting horse owners’ choice of nutritional supplements for dressage and eventing horses. An online questionnaire was distributed to owners/riders of dressage and/or event horses to collect data on the demographics of the owner/rider and their horses, the sources of information used when choosing nutritional supplements and their opinion on these different sources. Data analysis included descriptive analysis and categorisation of free text. χ2 tests were used to explore factors affecting decision-making. In total, 757 responses were analysed. Participants obtained information on nutritional supplements from vets (49.8 per cent), internet article/review (39.4 per cent), other horse owners (38.7 per cent), coach/trainer (36.5 per cent) and nutritionists (33.4 per cent). They ranked the most reliable sources of information as vets, followed by nutritionists, then research studies, and the most influential sources of information as vets, followed by coach/trainer and nutritionists. Most participants had used other horse owners as their source of information for their most recent supplement. The age of the owner, competitive discipline, their educational qualification and their riding experience were significantly associated with aspects of decision-making. The study also identified a need for independent, unbiased sources of information on nutrition and supplements in the horse.